Dinâmica do carbono em florestas tropicais brasileiras extra-amazônicas - Maia, Vinícius Andrade (2021)
The Earth’s ecosystem functioning has been dramatically altered by climate change and human activities over the recent decades. Therefore, it is urgent to understand the ecosystems responses to these changes. In the earth system, forests play an important role in many ecosystem functions, among them the primary net productivity and carbon cycling. However, these functions have been affected by changes in climate and increasing CO2 emissions, in a way that the provision of these ecosystem services may be compromised in the next decades. These changes may affect the whole planet dynamics, and therefore species survival and human well-being. The aim of this study was to understand the spatial and temporal patterns of carbon stocks and sinks of tropical forests in southeastern Brazil. These results contribute to knowledge of the functionality of tropical forests and its biomes and assist in conservation policies and decision making to protect the terrestrial biota.